2019
DOI: 10.3389/fnmol.2019.00292
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine and the Smart Drug 3,4-Methylenedioxypyrovalerone (MDPV) Induce Generalization of Fear Memory in Rats

Abstract: Human studies have consistently shown that drugs of abuse affect memory function. The psychostimulants amphetamine and the “bath salt” 3,4-methylenedioxypyrovalerone (MDPV) increase brain monoamine levels through a similar, yet not identical, mechanism of action. Findings indicate that amphetamine enhances the consolidation of memory for emotional experiences, but still MDPV effects on memory function are underinvestigated. Here, we tested the effects induced by these two drugs on generalization of fear memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Importantly, susceptible rats explored less the Open Field arena for all the test duration, whereas the NRs and resilient ones moved less at the beginning but started to explore more the arena towards the end of the test displaying an opposite habituation profile with respect to rats not exposed to trauma. This phenotype-specific habituation profile has a high translational value and may be ascribable to fear generalization induced by the traumatic experience, which are key features of PTSD and which consist in the transfer of fear to stimuli not related to the aversive event 34 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, susceptible rats explored less the Open Field arena for all the test duration, whereas the NRs and resilient ones moved less at the beginning but started to explore more the arena towards the end of the test displaying an opposite habituation profile with respect to rats not exposed to trauma. This phenotype-specific habituation profile has a high translational value and may be ascribable to fear generalization induced by the traumatic experience, which are key features of PTSD and which consist in the transfer of fear to stimuli not related to the aversive event 34 37 .…”
Section: Discussionmentioning
confidence: 99%
“…in a volume of 1 ml/kg, immediately after the training trial. Doses were chosen on the basis of pilot experiments performed in our laboratory and on literature data ( Roozendaal et al, 1996 ; Colucci et al, 2019 ). The solutions were freshly prepared on the day of the experiment and protected from exposure to light.…”
Section: Methodsmentioning
confidence: 99%
“…While it generally enhances memory consolidation, it has been shown that it increases memory retrieval errors and alters working memory performances ( Martinez et al, 1980a ; Ballard et al, 2014 ; Bardgett et al, 2019 ). Interestingly, it has been shown that amphetamine effects on memory consolidation are dependent on the amphetamine-induced activation of the noradrenergic system ( Lee and Ma, 1995 ; Colucci et al, 2019 ), a neurotransmitter system critically involved in the modulation of long-term memory consolidation ( Ferry et al, 1999 ; Roozendaal and McGaugh, 2011 ; McLumiere et al, 2017 ). We recently demonstrated that the dissociative drug ketamine enhances memory performance through a mechanism that activates both the central and peripheral noradrenergic signaling ( Morena et al, 2017 ; Morena et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical studies identified further consequences of MDPV use such as hypertension, chest pain, hyperthermia, persecutory delusions, tachycardia, aggressiveness, and suicidal thoughts [ 19 , 20 , 21 , 22 ]. MDPV inhibits the reuptake of norepinephrine, serotonin and, mainly, dopamine, where this substance displays greater potency than amphetamine-like drugs [ 23 ]. Although intranasal route seems to be the most established administration route, others include oral, rectal, intravenous, and even inhalation.…”
Section: Introductionmentioning
confidence: 99%